The Effectiveness of Using Short Stories on Developing Some Creative Reading Skills for University Students - Abdulaziz Morsy Ahmed, Emad; Mahmoud Mabrouk Abdellatif, Hossam; Elsayed Mohammed, Rabah (Technium Social Sciences Journal, 2024)
The present study aimed to investigate the effectiveness of using short stories for developing creative reading skills for Jazan University students. The current study used the quasi-experimental research design. The researchers divided the participants into two groups. The experimental group used short stories, while the control group did not receive any training except for the traditional approach. The main question raised in this research is ‘what is the effectiveness of using short stories on developing some creative reading skills among Jazan University students?’ To this end, the researcher collected data through a creative reading skills test. Furthermore, a model of the teaching program, based on using short stories, was improved and tested with a group of students in Jazan University in Kingdom of Saudi Arabia. The results of the present research showed that there are statistically significant differences between the mean scores of the experimental group students and those of the control group students in both creative reading skills and overall creative reading in favor of the experimental group. The results revealed that using short stories helped the experimental group students develop their creative reading skills and overall creative reading more effectively than those of the control group who were taught using the traditional way. The conclusion of the current research showed that the traditional way used in teaching reading skills in EFL classrooms should be developed to help students improve their reading skills.